2006
DOI: 10.1051/0004-6361:20054085
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of the optical-afterglow luminosities of long gamma-ray bursts

Abstract: We studied the optical afterglows of the 24 pre-SWIFT gamma-ray bursts (GRBs) with both known spectroscopic redshift and published estimates of the optical extinction in the source frame. We found an unexpected clustering of the optical-afterglow luminosities measured 12 h (source frame time) after the trigger. For 21 out of 24 bursts, the distribution of the optical luminosities is narrower than the distribution of the X-ray luminosities, and even narrower than the distribution of the ratio between the monoch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(128 citation statements)
references
References 93 publications
11
113
4
Order By: Relevance
“…In the late afterglow, ν i < ν c (the slow cooling regime) and the optical wavelength range is located either above or below ν c , which is fully supported by current observations (e.g. Galama & Wijers 2001;Stratta et al 2004;Nardini et al 2006;Schady et al 2007;Greiner et al 2011). Two prominent signatures, the Ly-α and Lyman-limit break at 121.5 × (1 + z) nm and 91.2 × (1 + z) nm respectively, and their characteristic redshift-dependent prominence, allow for a robust and precise redshift determination.…”
Section: Introductionsupporting
confidence: 85%
“…In the late afterglow, ν i < ν c (the slow cooling regime) and the optical wavelength range is located either above or below ν c , which is fully supported by current observations (e.g. Galama & Wijers 2001;Stratta et al 2004;Nardini et al 2006;Schady et al 2007;Greiner et al 2011). Two prominent signatures, the Ly-α and Lyman-limit break at 121.5 × (1 + z) nm and 91.2 × (1 + z) nm respectively, and their characteristic redshift-dependent prominence, allow for a robust and precise redshift determination.…”
Section: Introductionsupporting
confidence: 85%
“…The simplest observation is that the luminosity light curves, in both the X-ray and optical/UV samples, show clustered behaviour. Evidence for clustering into two groups, at ∼ 0.5 − 1 day, for the optical/IR GRB afterglows was reported by Boër & Gendre (2000); Gendre & Boër (2005); Nardini et al (2006); Liang & Zhang (2006); Nardini, Ghisellini & Ghirlanda (2008); . However, several more recently published works have suggested that the afterglow distributions are unimodal (Melandri et al 2008;Cenko et al 2009a;Oates et al 2009;Kann et al 2010;Melandri et al 2014).…”
Section: Introductionmentioning
confidence: 89%
“…It should, therefore, be kept in mind that the results presented in this paper apply to GRBs with low host galaxy extinction along the line-of-sight (A V < ∼ 1.0). In the case of selection effects against dim GRBs, our results will be affected if low-luminosity GRBs belong to a different class of GRB than to their high-luminosity counterparts, as suggested by Liang & Zhang (2006) and Nardini et al (2006Nardini et al ( , 2008; although see Oates et al 2009) so this possibility should be kept in mind. We, therefore, stress that the results presented in this paper may not apply to low-luminosity and/or highly extinguished GRBs.…”
Section: Samplementioning
confidence: 96%